2003
DOI: 10.1021/nl034666d
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanodisk Growth by Surface Plasmon Enhanced Photoreduction of Adsorbed [Ag+]

Abstract: The photoreduction of silver ions by citrate, catalyzed on silver seeds, is used to synthesize disk-shaped silver nanoparticles in solution. The reaction is characterized by transmission electron microscopy (TEM), atomic force microscopy (AFM), optical absorption spectroscopy, and by measuring the silver ion concentration during the reaction. The irradiation wavelength determines the final shape of these particles due to the shape dependence of the Ag plasmon spectrum. The quantum yield of this reaction has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
482
1
27

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 525 publications
(528 citation statements)
references
References 29 publications
18
482
1
27
Order By: Relevance
“…1 The irradiation wavelength controls the particle shape. Plasmon excitation can also photocatalyze small Ag colloid reformulation into large truncated prisms, and even fusion of such prisms into yet larger prisms.…”
Section: Introductionmentioning
confidence: 99%
“…1 The irradiation wavelength controls the particle shape. Plasmon excitation can also photocatalyze small Ag colloid reformulation into large truncated prisms, and even fusion of such prisms into yet larger prisms.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, surfactant-directed synthesis has enabled the high-yield production of gold nanorods [15,16], which are also tunable [17]. Silver nanoparticles can be synthesized with controlled shape and optical properties guided by optical illumination [18]. More complex architectures have also been described, including gold nanocages [19][20][21], elongated core-shell geometries [22] and gold nanostars [23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…Scientist gained significant control both the over size [7] and surfaces [8][9][10][11][12] for nanoparticles. They have demonstrated that anisotropy in nanostructure like triangular prisms [13][14][15][16][17][18], nanoscale rods [19][20][21][22][23][24][25][26], nanoshells [27][28][29][30][31], multipods [32][33][34], disks [35][36][37][38][39] and cubes [40][41][42] shows better performance over solid spheres. …”
Section: Nanomaterials and Nanotechnologymentioning
confidence: 99%